ANALISIS PEMASARAN BUAH PEPAYA DI DESA MATUNGKAS KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Juneke Marisa Sambuaga; Rine Kaunang ., Kaunang; Grace A. J. Rumagit A.J. Rumagit (AGRI-SOSIOEKONOMI, 2016)
This study aimed to describe marketing papaya fruit on each marketing channel in the village Matungkas Village, North Minahasa District. The research was conducted from February to April 2016. The data used are primary data. The research was done by using purposive sampling with the total number of respondents 45 people. Analysis of the data used is descriptive to portray marketing channels and marketing margin analysis and farmer share. The results showed that there are three patterns of marketing channels, namely: (1) marketing channels first (farmer-traders-retailers) with a marketing margin on the first channel of Rp 8.64 million / trip and farmer share of 40.00 percent. (2) a second marketing channel (farmers, retailers, the district / province) with a marketing margin on retailers in the district amounted to Rp 4,200,000 and farmer share of 58.82 percent, while the marketing margin on retailers in the province amounted to Rp 9.6 million / trip and farmer share of 50.00 percent. (3) The third marketing channel (farmer-consumer) with a marketing margin of Rp 2,400,000 and farmer share 100 percent. The most efficient marketing channel is channel marketing and channel marketing two third is the channel which is very profitable for farmers.